Analysis of personal financial management behavior in higher education student - Tasman, Abel; Efendi, Deny Ari; Masdupi, Erni (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Padang, 2018)
Personal financial management behavior is one of the interesting topics in financial management because in practice there are links with other science such as psychology and sociology. This research aimed to analyze the influence of (1) financial knowledge (2) internal locus of control and (3) parental income on personal financial management behavior. The population in this research are undergraduate students in the Faculty of Economics, Universitas Negeri Padang consists of 1,658 students. The samples were selected by using a clustered random sampling to get as much of the total samples of 100 students. The data of this research are primary and secondary data. The data were analyzed by Structural Equation Modeling (SEM) The results of this research show: (1) financial knowledge has a negative and no significant effect on personal financial management behavior of undergraduate students in the Faculty of Economics, Universitas Negeri Padang (2) internal locus of control has a positive and significant effect on personal financial management behavior of undergraduate students in the Faculty of Economics, Universitas Negeri Padang (3) parental income has a positive and no significant effect on personal financial management behavior of undergraduate students in the Faculty of Economics, Universitas Negeri Padang.Keywords: Behavior finance; financial knowledge; internal locus of control; parental income